POLITICAL WILL PEMERINTAH INDONESIA DALAM PEMBENTUKAN OMNIBUS LAW DAN ANALISA DAMPAK UNDANG-UNDANG CIPTA KERJA TERHADAP PENGUSAHA DAN PEKERJA - Jonatan, Ronaldo Marcelo Jonatan; Hulman Panjaitan; Wetmen Sinaga (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
President of the Republic of Indonesia Joko Widodo in his inauguration speech on October 20, 2019, stated his plan regarding the formulation of the Omnibus Law with the DPR. Several important points are the main reasons for the problems in the preparation of this law. Some of the points of the problem are regarding employee rights such as the deduction of severance pay to workers who are subject to termination by the company, the abolition of maternity leave and so on. Therefore, many workers / laborers and some elements of society reject the existence of this Job Creation Bill. This shows that there is a dynamic in the formation of the Omnibus Law or the Job Creation Law, be it formal or material rejection. The formulation of the problem in this research is (1) What is the basis for the Indonesian government to make changes to labor regulations in the Job Creation Law? and (2) What is the impact of changes to labor regulations in the Job Creation Law on employers and workers/workers with work relations? The research used is normative research (normative juridical) or also called doctrinal research, also referred to as literature research or document study research. From the results of the research, the problem of the Job Creation Law is also highlighted because it is considered that in its formation stage, it is considered not to heed the aspirations and participation of the community as mandated in Article 96 of Law Number 15 of 2019 concerning the Establishment of Laws and Regulations. The weakness of the Job Creation Law, in regulating the normative rights of labor compared to Law Number 13 of 2003 is that the Job Creation Law is very detrimental to workers / laborers because there are many articles that eliminate each other's articles, working time and overtime are longer, vacation time minus the minimum wage is lost, the wage calculation changes, the Wage for Menstrual and Maternity Leave will be lost, long leave is gone, unilateral layoffs are eased, severance pay is reduced.